Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ma16165647
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Properties of Polyester, Polylactide, and Cotton Nonwovens and Fabrics, by Means of Stable Aqueous Dispersions Containing Copper Silicate and Some Metal Oxides

Abstract: Literature reviews have described the applications of silver, copper, and zinc ions and metallic particles of Cu, Ti, and Zn oxides, which have been found to be useful antimicrobial reagents for the biofunctionalization of various materials and their surfaces. For this purpose, compositions of water dispersions containing emulsions of synthetic copolymers based on acrylic and vinyl monomers, polysaccharides (hydroxyethyl cellulose and starch), and various additives with wetting and stabilizing properties were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Both oxidants also exhibit antiviral potential [ 117 , 118 ]. There were also papers on the antibacterial cotton fabric prepared with other antibacterial agents [ 119 , 120 , 121 , 122 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both oxidants also exhibit antiviral potential [ 117 , 118 ]. There were also papers on the antibacterial cotton fabric prepared with other antibacterial agents [ 119 , 120 , 121 , 122 ]…”
Section: Resultsmentioning
confidence: 99%
“…Both oxidants also exhibit antiviral potential [117,118]. There were also papers on the antibacterial cotton fabric prepared with other antibacterial agents [119][120][121][122] The results of the microbiological tests (Table 10) indicated that the gas-phase bleaching process of cellulose samples using oxidising agents like ozone and vaporised hydrogen peroxide resulted in high biocidal efficiency against Gram (+) S. aureus (ATCC 6538) and Gram (-) E. coli (ATCC 11229) bacteria strains. The use of VHP was also applied earlier in the process of waste-free, low-temperature bleaching with simultaneous disinfection [Gram (+) and Gram (-) bacteria, moulds, fungi and spore forms] of cellulose fibre materials [47].…”
Section: Microbiological Assessment Of the Decontamination Efficiencymentioning
confidence: 99%
“…In spite of the high medical potential of both components of the PLA-Zn (ZnO), only a few papers concerning the biochemical investigations of this type of composite have been published [110][111][112][113][114][115][116][117].…”
Section: Introductionmentioning
confidence: 99%
“…These have been mainly focused on the antimicrobial properties of PLA-Zn (ZnO) composites [110][111][112][113][114][115][116][117], but also concerning their influence on osteoblasts and bacterial cell behavior in vitro (PLA-ZnO-Ag) [113], on cytotoxicity using ST-2 bone marrow cells (PLA-ZnO) [116] and on cell viability and proliferation (PLA-ZnO-SiO2) [111].…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial (antibacterial and antifungal) properties of the textile materials (fabrics and non-wovens) functionalized with the above-mentioned active agents exhibiting antimicrobial properties (CuSiO 3 , TiO 2 , ZnO, or ZnO•SiO 2 ) were highly dependent on the content of the agents in water dispersions. These new functionalized, non-woven polymeric textile materials can find practical applications in manufacturing filters for hospital air conditioning systems, the automotive industry, and air purification devices [20]. Gabbay et al conferred that cotton and polyester fibers exhibit a broad spectrum of properties against bacteria, viruses, and fungus using impregnation or coating with cationic copper.…”
Section: Introductionmentioning
confidence: 99%